Analysis of Eye Safety of repetitively pulsed laser products operating in MWIR, LWIR and FIR wavelength range - Młyńczak, Jarosław (International Journal of Electronics and Telecommunications, 2026)
Repetitively pulsed lasers operating in the MWIR, LWIR and FIR spectral regions are increasingly used in a wide range of applications, particularly in the form of semiconductor sources valued for their stability, efficiency and compactness. Ensuring the safe use of such devices requires accurate classification in accordance with IEC/EN 60825-1 standard, a process that becomes complex when multiple emission parameters such as pulse duration, repetition rate and peak power vary simultaneously. Although the standard provides general guidance and limited examples, it does not fully address all possible parameter combinations encountered in practical systems. This work presents a simplified analysis of the safety classification of repetitively pulsed lasers with variable parameters. A MATLAB-based simulation tool was developed to explore classification outcomes within defined parameter limits and to generate classification maps as a function of peak power and pulse repetition rate. The approach offers a clearer understanding of how change of parameters influences classification and provides a foundation that can be extended to broader parameter ranges and more diverse laser systems.